Effects of executives' pro-environmental education and knowledge sharing activities on eco-friendly agricultural production: Evidence from China. (1st April 2023) - Xie, Yu; Chen, Zhen; Tang, Hongjuan; Boadu, Francis; Yang, Yang
Abstract: With the development of urbanization, the emergence of climate change, and the increase in global population, agricultural production resources are facing enormous environmental pressure for survival and sustainability. Irrefutable impacts of these phenomena on agricultural production resources are recently recognized by environmental stakeholders to develop cleaner and sustainable models to address the challenges. From the environmental innovation and sustainable development perspective, academicians have considered executives' pro-environmental education as a vital mechanism for improving agricultural production resources. For instance, to publicize or promote the concept of agricultural ecological protection, government departments often organize relevant corporate executives to participate in environmental protection courses and training, and environmental knowledge exchange activities, among others in the quest to improve agriculture resources. However, how and under what conditions executives' pro-environmental education, training, and knowledge exchange activities influence agricultural production resources is still unclear and limited in the extant studies. Drawing on the knowledge-based view, this study constructed a research framework to examine the influence of executives' pro-environmental education on eco-friendly agricultural production. The study conducted empirical tests using data from 227 Chinese agricultural enterprises through regression and bootstrap analysis. The result shows that executives' pro-environmental education facilitates eco-friendly agricultural production by promoting the mediating variable managerial environmental concerns, and knowledge sharing activities positively moderates the mediating role of managerial environmental concerns in the relationship between executives' pro-environmental education and eco-friendly agricultural production. This scholarship is one of the rare attempts to scrutinize the integrated impact of executives' pro-environmental education, eco-friendly agricultural production, managerial environmental concerns, and knowledge-sharing activities in the domain of environmental sustainability. It explicitly offers new insights into the existing literature on environmental sustainability; further provides a policymaking reference for the improvement of agricultural enterprises' cleaner production activities. Graphical abstract: Image 1 Highlights: Executive pro-environmental education as an antecedent to eco-friendly agricultural production is introduced. Environmental concerned managers tend to adopt eco-friendly agricultural production approach more frequently. Knowledge-sharing activities and executive pro-environmental education foster environmental protection.